Effective stunting prevention: Empowering maternal nutrition education in rural Indonesia through AKUR PENTING intervention - Yuliantie, Putri; Ningrum, Novalia Widiya; Istiqamah (Health Sciences International Journal, 2024)
Background: Stunting remains a significant public health issue in Indonesia, particularly in rural regions such as Bangun Harjo Village, Central Kalimantan. Stunting affects not only physical growth but also cognitive development, leading to long-term impacts on productivity, health, and quality of life. Despite various government interventions, stunting continues to prevail due to poor maternal nutrition knowledge, inadequate feeding practices, and socio-economic challenges. Case presentation: In Bangun Harjo Village, high stunting rates among toddlers are largely attributed to improper complementary feeding (MPASI) and limited maternal understanding of nutrition. The Kupang Island Health Center initiated a community service intervention called "AKUR PENTING" (Stunting Prevention Kitchen Action) aimed at educating postpartum mothers and mothers of toddlers about proper feeding practices using locally available, nutrient-rich foods. The program included cooking demonstrations, distribution of educational materials, and active involvement of local healthcare workers. Discussion: The intervention significantly improved maternal knowledge about nutrition, with participants showing enthusiasm and engagement in learning how to prepare balanced meals. However, sustained behavior change and addressing broader socio-economic issues such as poverty and food insecurity remain challenges. Community-based interventions, combined with government support and policies, are critical to ensuring long-term success in reducing stunting. Conclusion: The AKUR PENTING intervention demonstrated the importance of maternal education and community engagement in stunting prevention. While the program successfully increased awareness and practical skills, comprehensive, multi-sectoral efforts are necessary to address the root causes of stunting, including socio-economic disparities and food insecurity.